Static and dynamic axial crush performance of in-situ foam-filled tubes - Duarte, Isabel (2019)
The aim of this paper is to study the quasi-static and dynamic compressive crush performance of newly developed in-situ foam-filled tubes (FFTs) made of light aluminium alloys prepared by powder compact foaming technique. By this method, the aluminium alloy empty tube is filled with an aluminium alloy foam during its formation. An extruded precursor of aluminium alloy and titanium hydride powder (0.5 wt.%) has been used for this purpose. The axial mechanical crushing behaviour and the failure mechanisms were assessed by uniaxial compression tests coupled with infrared thermography. The axial crush performance of in-situ FFTs was compared with performance of the individual components (integral-skin foam and empty tubes) submitted to the same heat treatment used to prepare the FFTs. Results confirm that the in-situ FFTs have a more stable axial crush performance. The results also demonstrate that heat treated aluminium alloy structures ensure high ductility and very good crashworthiness since they deform without formation of cracks during compression, which is a pre-requisite for good and reliable crashworthiness behaviour.